2016
DOI: 10.1111/nyas.13081
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine toxicity: a story of disrupted mitochondrial metabolism

Abstract: Rodenticides and pesticides pose a significant threat, not only to the environment, but also directly to humans by way of accidental and/or intentional exposure. Metal phosphides, such as aluminum, magnesium, and zinc phosphides, have gained popularity owing to ease of manufacture and application. These agents and their hydrolysis by-product, phosphine gas (PH3), are more than adequate for eliminating pests, primarily in the grain storage industry. In addition to the potential for accidental exposures in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 50 publications
(103 reference statements)
1
65
0
Order By: Relevance
“…In our case, we used virgin olive oil to induce antioxidant activity. According to an article published in 2016, more aggressive gastrointestinal decontamination is necessary for patients [4]. Different studies in rats [14] and humans [15] have revealed that N-acetylcysteine can help as it replenishes cellular glutathione and magnesium, in addition to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, we used virgin olive oil to induce antioxidant activity. According to an article published in 2016, more aggressive gastrointestinal decontamination is necessary for patients [4]. Different studies in rats [14] and humans [15] have revealed that N-acetylcysteine can help as it replenishes cellular glutathione and magnesium, in addition to its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…It progressively converts oxyhaemoglobin to methaemoglobin and hemi chrome species. The reaction of phosphine with oxyhaemoglobin leads to a formation of phosphite and phosphate ions [4]. Phosphine thus reduces the oxyhaemoglobin of blood.…”
Section: Introductionmentioning
confidence: 99%
“…More than 90% of these poisonings are related to suicide . A three‐gram tablet can produce one gram of phosphine (PH 3 ) gas, which is a colourless and odourless toxic gas …”
Section: Introductionmentioning
confidence: 99%
“…PH 3 is a highly toxic metabolic poison that affects all organs of the body and causes a wide range of effects including cellular poisoning, oxidative stress, cholinesterase inhibition, circulatory failure, cardiac toxicity, pulmonary toxicity and gastrointestinal (GI) tract damage, liver damage, neurotoxicity and electrolyte imbalance. It has been shown that cardiac tissue is one of the main target organs for the toxicity of PH 3 . In this regard, AlP has shown to induce significant deterioration in cardiovascular anatomy and functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation